Bermain Dengan Media TASRU (Kertas Kokoru) Untuk Mengembangkan Motorik Halus Anak - Dini Oftaviani; Shofitri Christina Dianita; Cari Riskiana; Intan Prastihastari Wijaya (Efektor, 2021)
Fine motor skills are very useful for children to complete activities in life, especially those related to skills. Fine motor development will train children to be skilled in using their hands and fingers and coordinating their eyes in a balanced way. However, children's fine motor skills will not develop just like that, so that if there is no stimulus from an early age, the child's fine motor skills will be very low. To overcome this, the activity of playing with tasru media (paper kokoru) provides the latest solution related to the development of children's fine motor skills. Based on these problems, this study aims to develop fine motor skills in early childhood by playing using Tasru media (Kokoru Paper). This study uses the Kemmis and Taggart model of classroom action research which consists of four stages, namely planning, implementation, observation, and reflection which is carried out in 3 cycles, namely Cycle I, Cycle II, and Cycle III. Based on the data obtained in the first cycle of 50% which is classified in the category is still low. Furthermore, in the second cycle there was an increase of 14% so that it became 64% but did not meet the learning completeness criteria. Then in the third cycle there was another increase of 19% so that the achievement of the percentage in the third cycle was 83% and had exceeded the learning mastery of 75%. So it can be concluded that playing with Tasru media (Kertas Kokoru) can develop fine motor skills of children in group B PAUD (KB) AL-FIKR Banaran Kediri City.